Relativistic Magnetic Reconnection in Electron-Positron-Proton Plasmas: Implications for Jets of Active Galactic Nuclei - Petropoulou, Maria; Sironi, Lorenzo; Spitkovsky, Anatoly; Giannios, Dimitrios (The Astrophysical Journal, 2019)
Magnetic reconnection is often invoked to explain the nonthermal radiation of relativistic outflows, including jets of active galactic nuclei (AGNs). Motivated by the largely unknown plasma composition of AGN jets, we study reconnection in the unexplored regime of electron-positron-proton (pair-proton) plasmas with large-scale two-dimensional particle-in-cell simulations. We cover a wide range of pair multiplicities (lepton-to-proton number ratio κ = 1-199) for different values of the all-species plasma magnetization (σ = 1, 3, and 10) and electron temperature ({{{Θ }}}e\equiv {{kT}}e/me{c}2=0.1{--}100). We focus on the dependence of the post-reconnection energy partition and lepton energy spectra on the hot pair plasma magnetization {σ }e,h (i.e., the ratio of magnetic to pair enthalpy densities). We find that the post-reconnection energy is shared roughly equally between magnetic fields, pairs, and protons for {σ }e,h ≳ 3. We empirically find that the mean lepton Lorentz factor in the post-reconnection region depends on σ, Θ e , and {σ }e,h as < {γ }e-1> ≈ \sqrt{σ }(1+4{{{Θ }}}e)≤ft(1+{σ }e,h/30\right), for σ ≥ 1. The high-energy part of the post-reconnection lepton energy distributions can be described by a power law, whose slope is mainly controlled by {σ }e,h for κ ≳ 3-6, with harder power laws obtained for higher magnetizations. We finally show that reconnection in pair-proton plasmas with multiplicities κ ∼ 1-20, magnetizations σ ∼ 1-10, and temperatures Θ e ∼ 1-10 results in particle power-law slopes and average electron Lorentz factors that are consistent with those inferred in leptonic models of AGN jet emission.
Keywords: acceleration of particles; Astrophysics - High Energy Astrophysical Phenomena; galaxies: active; magnetic reconnection; PLASMAS